Demokratisasi Konvensi HAM Relasi Islam dan Negara: Kondisi Indonesia - Abdul Jalil Salam (Media Syari'ah, 2012)
This study aims to look at the Indonesian government’s strategy in improving the process of Human rights democratization. Democracy and human rights are two things that can not be separated. However this study has found that besides providing legal penalties to the perpetrators, Indonesian government should also pay attention to the development of social dynamics and the tendency of other countries to understand human rights issues. In this study the author recommend that holistic paradigm is a suitable paradigm offered in human rights issues to be developed in Indonesia.